1929 [large type] : inside the greatest crash in Wall Street history--and how it shattered a nation - Sorkin, Andrew Ross (Random House Large Print, 2025)
This book examines the events surrounding the United States stock market crash of 1929 and the economic conditions that contributed to the onset of the Great Depression. Drawing on historical records and archival research, the author reconstructs the period leading up to the collapse and the interactions among financial leaders, government officials, and market participants. Focusing on the relationship between Wall Street and Washington, the narrative explores the roles of speculation, policy decisions, and public confidence in shaping the crisis. The book places the crash within a broader historical context, emphasizing recurring patterns in financial markets and the social and political consequences of large-scale economic upheaval.